Assessment of cardiac function in rat endovascular perforation model of subarachnoid hemorrhage; A model of subarachnoid hemorrhage-induced cardiac dysfunction - Munakata, Masahito; Kanazawa, Hideaki; Kimura, Kensuke; Arai, Takahide; Sukegawa, Hiroaki; Fukuda, Keiichi (Frontiers in Synaptic Neuroscience, 2022)
Although the association between cardiac dysfunction and subarachnoid hemorrhage (SAH) has been recognized, its precise underlying mechanism remains unknown. Furthermore, no suitable animal models are available to study this association. Here, we established an appropriate animal model of SAH-induced cardiac dysfunction and elucidated its mechanism. In this rat model, contrast-enhanced computed tomography of the brain confirmed successful induction of SAH. Electrocardiography detected abnormalities in 55% of the experimental animals, while echocardiography indicated cardiac dysfunction in 30% of them. Further evaluation of left ventriculography confirmed cardiac dysfunction, which was transient and recovered over time. Additionally, in this SAH model, the expression of the acute phase reaction protein, proto-oncogene c-Fos increased in the paraventricular hypothalamic nucleus (PVN), the sympathetic nerve center of the brain. Polymerase chain reaction analysis revealed that the SAH model with cardiac dysfunction had higher levels of the macrophage-associated chemokine (C-X-C motif) ligand 1 (CXCL-1) and chemokine (C-C motif) ligand 2 (CCL-2) than the SAH model without cardiac dysfunction. Our results suggested that SAH caused inflammation and macrophage activation in the PVN, leading to sympathetic hyperexcitability that might cause cardiac dysfunction directly and indirectly. This animal model may represent a powerful tool to investigate the mechanisms of the brain-heart pathway.